Development of a Non-Textbook with SDGs Framework to Enhance Students’ Scientific Literacy - Sinta Srie Wulan; Bibin Rubini; Didit Ardianto (Universitas Negeri Semarang, 2026)
This study aims to develop and evaluate the feasibility and effectiveness of the non-textbook Persahabatan Besi dan Magnet as an innovative learning material to enhance junior high school students’ scientific literacy. The book was created using a Discovery Learning approach integrated with narrative, visual, and experiential elements, and aligned with Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 7 (Affordable and Clean Energy), and SDG 12 (Responsible Consumption and Production). The research followed Borg and Gall’s Research and Development (R&D) model, which includes needs analysis, product design, expert validation, limited trials, and effectiveness testing. Participants consisted of 30 students and three science teachers from a junior high school in Sukabumi, Indonesia. Data were collected through questionnaires, expert validation forms, teacher and student response surveys, and a scientific literacy test covering competence, knowledge, context, and attitude. Expert validation showed that the book met the “very good” category, especially in content accuracy and conceptual depth. Teacher and student responses were highly positive, noting clear language, visual appeal, and contextual relevance. Effectiveness testing demonstrated a significant improvement in scientific literacy, supported by medium N-Gain and a very large effect size. These results indicate that the book is a feasible and effective alternative learning resource.